The effects of changes in the coastline and water depth on tidal prism and water exchange of the Laizhou Bay, China - Sun, Jiwei; Peng, Lihong; Zhu, Xingwang; Li, Zikang; Shi, Hongyuan; Zhan, Chao; You, Zaijin (Frontiers in Marine Science, 2024)
Laizhou Bay’s coastline has undergone multiple alterations due to human activities such as land reclamation and port construction. These changes in the coastline have led to modifications in the bay’s hydrodynamic conditions, which, in turn, can impact the marine environment and potentially result in a decline in biodiversity. To date, there has been no comprehensive study focusing on the coastline changes and hydrodynamic variations in Laizhou Bay. Therefore, this study utilizes coastline and water depth data from four time points—1990, 2003, 2013, and 2023—to establish a two-dimensional tidal current model of Laizhou Bay using Delft3D. Based on the good agreement between the simulated tidal current results and the observed data, this study further investigates the changes in tidal prism and water exchange in Laizhou Bay. The results indicate that tidal currents dominate the bay, with significant influences of topographic changes on the velocity and direction of tidal flows. The Eulerian residual current velocity is substantially lower than the tidal current velocity. Both tidal and residual currents play a role in controlling the distribution of materials within Laizhou Bay. Over the past three decades (1990-2023), the tidal prism in Laizhou Bay has shown a downward trend, with the tidal prism during spring, intermediate, and neap tides in 2023 reduced by 2.03%, 6.36%, and 10.19%, respectively, compared to 1990. The water exchange capacity has also weakened, with the half-exchange time being 71 days in 1990, increasing to 73 days in 2003 and 81 days in 2013, and showing a slight increase of 1 day in 2023 compared to 2013. Thus, changes in the coastline and water depth of Laizhou Bay can alter its hydrodynamic conditions, significantly impacting the tidal prism and water exchange, leading to a decrease in tidal prism and exchange rate, an increase in the water exchange period, a slower dispersion rate of pollutants, and a reduced water environmental carrying capacity. This research provides a scientific reference for protecting the marine environment and coastal management in Laizhou Bay.